Turkey in Afghanistan: A successful stakeholder, but a difficult partner - Cem Sey; Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2016)
The global increase in Islamist violence, state disintegration in Asia and Africa and the resulting influx of refugees to Europe are forcing the international community to intensify its focus on the promotion of peace in crisis regions and on social reconstruction. It may be useful to draw on the experiences in Afghanistan when responding to future challenges. Here, particular attention should be paid to Turkey, whose strategy and approach differ from those of other states, and whose involvement in Afghanistan is generally deemed successful. Simultaneously, the experiences gathered in Afghanistan also permit assertions to be made regarding Turkey as a partner in terms of security cooperation - a highly topical issue. (SWP Comments)
Keywords: 320